Pengaruh Strategi Green Marketing, Green Product dan Green Brand terhadap Keputusan Pembelian Produk Kecantikan Ramah Lingkungan: (Studi pada The Body Shop di Mojokerto) - Dwi Arviana, Nerissa; Baidlowi, Imam; Hidayat, M. Syamsul (Journal of Management and Social Sciences, 2024)
The beauty industry is a sector that continues to grow and plays an important role in the global economy. This phenomenon is driven by increasing consumer awareness of personal appearance and skin care. However, along with this growth comes concern over the beauty industry's negative impact on the environment and human health. To overcome these challenges, the concept of sustainability has become the main focus for beauty companies. One company in the beauty sector is The Body Shop, which has long been one of the pioneers in the beauty industry which is committed to sustainable and environmentally friendly principles. This research aims to find out and analyze the influence of green marketing strategies, green products and green brands on purchasing decisions for environmentally friendly beauty products (study at the body shop Mojokerto). The research method used in this research is a quantitative research method using SPSS software. This research is descriptive research. The sampling technique used is Probability Sampling using the Simple Random Sampling method. Data collection in this research used questionnaires from 110 respondents from The Body Shop consumers whose addresses were in Mojokerto. The data analysis method in this research uses validity testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results of this research show that green marketing strategies do not have a positive and significant effect on purchasing decisions, green products have a positive and significant effect on purchasing decisions, green brands have a positive and significant effect on purchasing decisions. Green marketing strategies, green products and green brands simultaneously influence purchasing decisions.